Cost-consequence analysis of Pharmaceutical Care program for systemic arterial hypertension in the public health system in Brazil - Maurílio de Souza Cazarim; Altacílio Aparecido Nunes; Leonardo Régis Leira Pereira (Universidade de São Paulo, 2018)
ABSTRACT In Brazil, 80% of hypertensive patients have no blood pressure controlled, this fact has caused severe financial consequences for the public health system (PHS) and the Pharmaceutical Care (PC) has emerged as an effective alternative. The aim of this study was to analyze the costs and outcomes of systemic arterial hypertension (SAH) for conventional assistance compared to assistance with PC in the PHS. This is a pharmacoeconomic study with cost-consequence analysis nested to clinical trial. Hypertensives patients were followed-up from 2006 to 2012. During 2009 they were assisted by the PC program in Ribeirão Preto-SP, Brazil. Clinical indicators, systolic and diastolic blood pressure (SBP and DBP), triglycerides, total cholesterol (TC) and its fractions and healthcare indicators, consumption of antihypertensive medication and consultations were analyzed. Costs were listed as direct medical and direct non-medical. The average cost of conventional care for 104 patients followed-up was US$ 198.97, in the PC period and after discharge was US$ 407.91 and US$ 214.96 patient/year. After discharge of patients from PC there was reduction of SBP, DBP, TC and cardiovascular risk, 9.4 mmHg, 4.6 mmHg, 12.0 mg/dL, and 23% [p<0.005], respectively. The PC program optimized clinical and healthcare indicators and impacted in the SAH costs for the PHS.